Analisis Gaya Bahasa dan Majas pada Lirik Lagu “Sampai Jadi Debu” Karya Banda Neira - Annisa Mazaya Fhatarani; Mirza Irdina (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This article contains an analysis of the language style and figures of speech in the lyrics of the song